If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36x + 3 = 5 Reorder the terms: 3 + 36x = 5 Solving 3 + 36x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 36x = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 36x = 5 + -3 36x = 5 + -3 Combine like terms: 5 + -3 = 2 36x = 2 Divide each side by '36'. x = 0.05555555556 Simplifying x = 0.05555555556
| (9x^2)-(x)+9=0 | | 10*3y-2=4y-y+8 | | 16.2-3.8g=-11.9g | | 7(5-x)=42 | | 6b^2+45b=0 | | 3+-3=3t+6 | | 0.7x-1=(-0.5x-0.7) | | 15.85+1.8y=-0.2y-18.67-1.08 | | (2x^2)-(9x)+10=0 | | -8s=-10s+14 | | 6x-9=39-2x | | -18b+1=17-16b | | -20-20+10p=20+13p | | 3x+8=2x+35 | | (-4)+3=14 | | Y+72=4(6+Y) | | 195-8y+y^2=180 | | 10c+8=9c | | 10-8r=-8-5r | | -9m-10=-1-7m+1 | | -5(-1x+8)=-45 | | x*.13=102 | | -7-3d=-2d | | (2n+19)+(4n+17)=180 | | 8+5n=7n-8 | | -8k=-10k+10 | | (2x+9)= | | (6x^2)-(5x)-6=0 | | 3-2h=-7-7h | | x+y^2=180 | | 3(7x+8)=-81 | | 8(6n-1)-7=-111 |